The comparison of peak oxygen uptake between swim-bench exercise and arm stroke - Ogita, F.; Taniguchi, S. (European Journal of Applied Physiology, 1995)
To compare maximal cardio-respiratory stress between swim-bench exercise (SB) and arm stroke (AS), peak oxygen uptake (VO2peak) was measured in six trained swimmers. The SB was performed at stroke frequency of 50.min-1. Oxygen uptake (VO2) was measured during exercise at 3-min constant exercise intensities in SB and at 4-min constant water flow rates in AS. We measured a steady-state VO2 within 3 or 4 min after the beginning of each exercise. The exercise intensity or the water flow rate was increased by 14.7 W or by 0.05 m.s-1, respectively, until a levelling-off of VO2 was observed. The VO2 was measured by the Douglas bag method. Heart rate (HR) and blood lactate concentration ([la-]b) were determined at the exercise intensity and the water flow rate at which VO2peak was obtained. At submaximal levels, VO2 increased in proportion to exercise intensity for SB and to the water flow rate for AS. A levelling-off of VO2 was observed in all subjects for both kinds of exercise. The VO2peak during SB [2.13 (SD 0.25)1.min-1] was significantly lower than that during AS [2.72 (SD 0.39)1.min-1] and corresponded to 78.9 (SD 7.0)% of AS VO2peak. Maximal HR during SB was also significantly lower than that during AS. No significant differences between SB and AS were found for either pulmonary ventilation or [la-]b. The peak exercise duration in SB [2.4 (SD 0.5) min] was significantly shorter than that in As [3.6 (SD 0.5) min]. These results would suggest that even though both kinds of exercise use the muscles of the upper body, active muscle groups involved during SB are different and/or smaller, and maximal stress on the cardio-respiratory system is lower when compared to AS.